Risk assessment of African swine fever transmission by spray-dried porcine plasma in piglet feed and the effect of UV irradiation treatment as an additional safety step - de Vos, Clazien J.; Heres, Lourens; Dekker, Aldo; Swanenburg, Manon; Pelser, W. Meindert; Post, Jacob; Hulst, Marcel M. (Frontiers in Veterinary Science, 2025)
The increase of African swine fever (ASF) outbreaks worldwide has raised concerns about the feeding of spray-dried porcine plasma (SDPP) to pigs. The processing of blood into SDPP should thus guarantee sufficient inactivation of ASF virus (ASFV) to render a safe product. The objective of this study was to evaluate (i) the required level of inactivation if blood of ASF-infected pigs would be processed into SDPP and fed to piglets, and (ii) the additional safety achieved if UV treatment is applied to plasma before spray-drying. A quantitative microbial risk assessment (QMRA) model was built to assess the infection probability (Pinf) of weaned piglets fed with SDPP produced from blood collected from a single ASF-infected herd. The inactivation of ASFV by UV treatment was quantified using a mobile, laboratory-scale “Cold Pasteurization” apparatus (Lyras inc, Aalborg, Denmark). Porcine plasma spiked with blood collected from pigs experimentally infected with ASFV was irradiated with different doses of UV-C and the log10 reduction factor (LRF) calculated. An average LRF of 2.2 was achieved by the highest dose of UV-C irradiation applied ( 137 Joule/m2). QMRA model results indicate that an LRF of 5 needs to be achieved during processing to arrive at a median value of Pinf < 0.01, i.e., less than 1 out of 100 ASF-infected batches resulting in new infections. With an LRF of 8, also the 95th percentile value of Pinf is < 0.01. These results were compared to reported LRF values of spray-drying and dry storage of SDPP, which varied between 5.2 and 11.1. Applying UV-C irradiation as an additional step in SDPP production thus provides extra safety guarantees as the combined inactivation levels of spray-drying, dry storage and UV treatment are likely to result in an overall LRF ≥ 8, implying a very low risk of new ASF infections (median Pinf 7.3 × 10−6; 95th percentile 1.6 × 10−3). The QMRA model did not account for the probability that ASF-infected pigs are unintendedly processed into SDPP. This probability is low if SDPP is not sourced from pigs in ASF-infected areas, therewith further reducing the ASF infection risk of SDPP.